Can Regulation Promote Financial Inclusion? - Chen, Rong (World Bank, Washington, DC, 2019)
Despite the commitments of the development community toward broader access to finance, financial inclusion rates worldwide are rather unsatisfactory. To date, around two billion adults do not have access to basic financial services such as savings and checking accounts. Attempting to bridge such gap between policy objectives and outcomes, several economists have probed the determinants of financial inclusion. This paper contributes to the debate by investigating the role played by financial regulation. First, the paper proposes a broad index of regulatory quality for financial inclusion, emphasizing the role of nontraditional delivery models, for example, branchless banking, and actors, for example, nonbank lending institutions. Second, the paper tests the relationship between regulatory quality and financial inclusion outcomes. The analysis finds that in countries where regulatory quality is within the top quartile, individuals are 12.4 percent more likely to have an account at a financial institution with respect to bottom quartile countries.